Primitive neuroectodermal tumor in advanced age: case report - Zavarize, Juliana de Almeida; Saito, Octávio Sakahara; Ferreira, Fernanda Proa; Leal, Frederico; Soares, Denise Junqueira Maia; Luiz, Juliano Manzoli Marques (Brazilian Journal of Oncology, 2020)
Objectives: Primitive neuroectodermal tumors (PNETs) are aggressive neuroectodermal neoplasms and are originated from neuroectodermal tissues. They belong to a larger group of tumors known as Ewing tumors and are unusual in adult population. This case reports PNET in the oldest patient quoted in literature and established it as a differential diagnose to soft tissue tumors in advanced age. Case report: Female, 69 years, with swelling and pain in the nasal cavity. Images revealed expansive mass with soft tissues density occupying paranasal sinuses, nasopharynx and rhinopharynx diminishing the air column. Histopathologic findings were compatible with PNET. Conclusion: Primitive neuroectodermal tumors are more often found in children. This current case report call attention to a 69-years-old woman with a PNET on nasopharynx. Once the patients' age and the disease site are both extremely unusual, this case report seeks to contribute to the diagnosis of rare PNETs presentation forms.
Keywords: Sarcoma; Ewing; Neuroectodermal tumors; Primitive; Soft tissue neoplasms